Cross-border price convergence: the case of the MERCOSUR - Samaniego Ruiz Diaz, Adriana (Kansas State University, 2009)
This paper empirically examines whether there is a tendency for trade-induced price convergence - in other words if price differences among city pairs separated by a border decline with increased levels of trade. The paper examines the prices of goods in cities across Brazil and Paraguay after the implementation of MERCOSUR. Evidence of a border effect - the failure of the law of one price - between Brazil and Paraguay is found. However, the data show that since the beginning of MERCOSUR, price dispersion between Brazil and Paraguay is less for those goods that are traded more between these partners.
Keywords: Price convergence; The law of one price; Economics, General (0501)